Design of an RF-DC conversion circuit for energy harvesting - Devi, K. K. A.; Md.Din, Norashidah; Chakrabarty, C .K.; Sadasivam, S. (IEEE, 2012)
The design of voltage multiplier module used for energy harvesting system from ambient at downlink radio frequency range (935.2 MHz-959.8 MHz) of GSM- 900 is presented. The function of this voltage multiplier circuit is to convert the RF energy signal into DC voltage that can be used to energize the low power electronic devices. The design was based on the Villard voltage multiplier circuit. A 4 -stage Schottky diode voltage multiplier circuit was designed, modeled, simulated, fabricated and tested for its performance. Multisim was used for the modeling and simulation work. Simulation and practical tests were carried out for various input power levels at the specified frequency band. The RF input power levels verses the output voltages at the nodes of the Villard network were recorded. The input for the voltage multiplier module was fed through an efficient matching network from an RF energy harvesting antenna which is designed at 377 Ω impedance. For a received signal of –27dBm (1.99) μW at the antenna modules produce a DC output voltage of 2.1 V across 100 kΩ load.